2010
DOI: 10.1074/jbc.m110.162156
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced Internalization and Recycling of the Human Neuropeptide Y2 Receptor Is Regulated by Its Carboxyl-terminal Tail

Abstract: Agonist-induced internalization of G protein-coupled receptors plays an important role in signal regulation. The underlying mechanisms of the internalization of the human neuropeptide Y 2 receptor (hY 2 R), as well as its desensitization, endocytosis, and resensitization are mainly unknown. In the present study we have investigated the role of carboxyl-terminal (C-terminal) Ser/Thr residues and acidic amino acids in regulating receptor internalization, arrestin interaction, and recycling by fluorescence micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 76 publications
(67 reference statements)
5
60
0
Order By: Relevance
“…In contrast, nonvisual arrestins show only a ϳ3-5-fold binding differential (14 -16, 19) and were reported to bind unphosphorylated receptors in response to their activation (42,(63)(64)(65)(66)(67)(68). Thus, it appears that non-phosphate binding elements likely contribute more significantly to the binding of non-visual arrestins to their cognate receptors.…”
Section: Receptor Discriminator Residues Are Crucial For the Binding mentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, nonvisual arrestins show only a ϳ3-5-fold binding differential (14 -16, 19) and were reported to bind unphosphorylated receptors in response to their activation (42,(63)(64)(65)(66)(67)(68). Thus, it appears that non-phosphate binding elements likely contribute more significantly to the binding of non-visual arrestins to their cognate receptors.…”
Section: Receptor Discriminator Residues Are Crucial For the Binding mentioning
confidence: 96%
“…Therefore, the observed changes in spin label mobility can be directly attributed to the effects of receptor binding. The spin labels attached to arrestin-2 at positions 68,70,71,73,167,191,234,238, and 246 become substantially immobilized upon binding to dark P-Rh. Strong immobilization of these surface residues suggests that the binding of P-Rh causes the residues to come into direct contact with either the receptor itself, the adjacent membrane, or with other arrestin elements.…”
Section: Mapping the Receptor Binding Surface Of Arrestin-2-anmentioning
confidence: 99%
“…Direct binding studies with arrestin-2 and arrestin-3 revealed that both nonvisual subtypes bind with fairly high affinity to inactive phosphorylated GPCRs, with this binding reaching 70 -80% of maximum achieved with corresponding active phosphoreceptors (60 -62). Therefore, to determine whether agonist-independent phosphorylation of GPCRs by GRK5 has any functional consequences, we examined arrestin recruitment in intact cells, using BRET between ␤2AR tagged with Renilla luciferase at the C terminus and arrestins tagged with Venus at the N terminus (35,36,40,63,64). The BRET ratio in these experiments was determined as described previously (35,36,63), but because we were primarily interested in GRK-dependent increase of arrestin recruitment, we calculated net BRET as an increase in BRET ratio in the presence of exogenous GRK, as compared with cells that only express endogenous GRKs along with tagged ␤2AR and arrestins.…”
Section: Phosphorylation Of Serotonin 5-ht2c Receptor By Grk5/6 Is Inmentioning
confidence: 99%
“…To establish a quantitative in vivo arrestin-3-JNK3 interaction assay, we included the same forms of arrestin-3 N-terminal-tagged with Venus, which worked very well in the BRET-based arrestinreceptor interaction assay (18,19,25,40,41) (Fig. 1).…”
Section: Receptor Binding Of Structurally Distinct Arrestin-3 Mutants-mentioning
confidence: 99%